Analysis and control of the photon beam position at PLS‐II. (19th February 2016) - Ko, J.; Kim, I.-Y.; Kim, C.; Kim, D.-T.; Huang, J.-Y.; Shin, S.
Abstract : The variation of the photon beam position in a beamline, which is a critical issue for user experiments, is analyzed and corrected through the correlation link with the electron beam position in the storage ring. Abstract : At third‐generation light sources, the photon beam position stability is a critical issue for user experiments. In general, photon beam position monitors are developed to detect the real photon beam position, and the position is controlled by a feedback system in order to maintain the reference photon beam position. At Pohang Light Source II, a photon beam position stability of less than 1 µm r.m.s. was achieved for a user service period in the beamline, where the photon beam position monitor is installed. Nevertheless, a detailed analysis of the photon beam position data was necessary in order to ensure the performance of the photon beam position monitor, since it can suffer from various unknown types of noise, such as background contamination due to upstream or downstream dipole radiation, and undulator gap dependence. This paper reports the results of a start‐to‐end study of the photon beam position stability and a singular value decomposition analysis to confirm the reliability of the photon beam position data.